Hepatitis B virus surface antigen (HBsAg) and antibody (anti-HBs) forming immune complexes in fulminant hepatitis - Manoel C.P. Soares; Gilberta Bensabath; Paulo R.B. Cartágenes; Max M. Alves; Fernando A.A. Silveira; Alexandre C. Linhares (Sociedade Brasileira de Medicina Tropical (SBMT), 1999)
This paper reports an unusual pattern of serological HBV markers and the presence of HBsAg/anti-HBs immune complexes in serum samples from two patients with fulminant hepatitis from the Brazilian Western Amazon Basin. The diagnosis was made by both serologic tests and demonstration of antigen/antibody complexes by transmission electron microscopy. Concurrent Delta virus superinfection is also discussed.